Body mass index (BMI) vs body fat percentage (BFP) as a relation to estimate players` physiological soccer adaptation profile - Zerf, M.; Mokkedes, M. I.; Bengoua, A. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: In a soccer game, a VO2max of 60 ml/kg/mln has been suggested as the minimum fitness requirement for male soccer players to play at elite level. While the average maximal oxygen intake for elite adult players are reported to be in the range of 55 to 69 ml/kg/mln. Although to predict the effective endurance training to Improve maximal oxygen uptake, recent research confirmed obesity in terms of Fat percentage is a better parameter than BMI for the prediction of low VO2max. On its scientific basis, our aims are to test BMI VS BFP as a relation to estimate players` physiological soccer adaptation profile. Methods: to archive this objective, 148 well-trained first division soccer players under 18 years, at the end ofthe preparatory phase before the start ofthe Algerian championship 2016-2017, took part In the study. Split Into two groups based on their VO2max under or supenor to 56 ml/kg/mln. As a protocol, based on the validity of Test Cooper to predict VO2max in the field. Acceptable by cooper institute as an index of physiological training response or as indicators of current training status.